2005
DOI: 10.1210/jc.2004-2187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Growth Hormone Supplementation on Adult Height in Turner Syndrome: Results of the Canadian Randomized Controlled Trial

Abstract: This is the first evidence from a randomized, controlled trial to adult height that GH supplementation with induction of puberty at a near physiological age increases the adult height of girls with Turner syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(74 citation statements)
references
References 24 publications
5
66
1
2
Order By: Relevance
“…More recently, a 2-year RCT evaluating the impact of GH initiation before age 4 years, and a double-blind, placebo-controlled trial to AH have been published (87,88). Patients with TS in the North American GH registration trials treated to (near-) AH had average gains vs concurrent control (83), baseline predicted/projected height or historical controls ranging from about 5 to 8 cm over periods ranging from 5.5 to 7.6 years (89, 90, 91); similar results were observed in the more recent placebo-controlled trial (87). These data indicate that height gain of about 1 cm per year of GH therapy is a reasonable expectation.…”
Section: Efficacy Of Gh Treatmentmentioning
confidence: 97%
See 2 more Smart Citations
“…More recently, a 2-year RCT evaluating the impact of GH initiation before age 4 years, and a double-blind, placebo-controlled trial to AH have been published (87,88). Patients with TS in the North American GH registration trials treated to (near-) AH had average gains vs concurrent control (83), baseline predicted/projected height or historical controls ranging from about 5 to 8 cm over periods ranging from 5.5 to 7.6 years (89, 90, 91); similar results were observed in the more recent placebo-controlled trial (87). These data indicate that height gain of about 1 cm per year of GH therapy is a reasonable expectation.…”
Section: Efficacy Of Gh Treatmentmentioning
confidence: 97%
“…Despite the plethora of studies of GH treatment in TS, a 2007 Cochrane Center review (82) identified only four trials in which GH treatment was compared in a randomized fashion with a concurrent non-treatment or placebo control for at least 1 year (83,84,85,86), and only a single RCT that followed participants to AH (83). More recently, a 2-year RCT evaluating the impact of GH initiation before age 4 years, and a double-blind, placebo-controlled trial to AH have been published (87,88).…”
Section: Efficacy Of Gh Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Without GH treatment, adult women with TS are on average 20 cm shorter than women without TS (2). Although TS is not associated with GH deficiency, supraphysiological GH doses increase adult height by 5-12 cm (3,4,5). Differences in efficacy of GH treatment can be explained by age at initiation and duration of therapy, compliance, estrogen therapy regimen, and several, partly unknown, genetic factors (4,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In past years it had been demonstrated that, in childhood, GH treatment with doses higher than those employed in GH deficiency can improve adult height (AH) in these patients (1,2,3). Therefore, it was widely accepted for many years that children with TS should be regularly treated with GH.…”
Section: Introductionmentioning
confidence: 99%